O discurso bíblico hierarquizante das traduções neotestamentárias: uma análise exegética e de discurso. - Pestana, Álvaro César (2021)
New Testament translations are subject to a hierarchical discourse that does not come from the fraternal and egalitarian environment of early Christianity. Based on this hermeneutic suspicion, we demonstrate through qualitative bibliographic research, how these translations were instrumentalized in the service of authoritarianism, which is not present in the Greek originals. A reading of the New Testament through exegesis and philology proves the fraternal, egalitarian, and non-hierarchical praxis in Christian communities. Early Christianity refused to adopt or adapt for itself the hierarchies of the social organization of the surrounding society so that this refusal is evident in the vocabulary used and in the social practices described and encouraged in the New Testament. The subsequent hierarchical discourse gradually imposed itself on Christianity over the centuries, introducing itself in the New Testament translations into Portuguese since the 17th century. Taking Discourse Analysis as a theoreticalmethodological path and through an analytical model adapted to our research object, we approached a corpus of nine New Testament texts in thirty-nine translations into the Portuguese language to highlight the elements of this hierarchy in the discourse hosted or promoted by the translators. The analysis of the hierarchical elements in the translations of the corpus allowed a comparative tabulation of the results. At the end, guidelines and proposals are presented for a hermeneutics that promotes non-hierarchical, fraternal, and egalitarian biblical translations, in line with the primitive Christian discourse and in contrast to the modern hegemonic hierarchical discourse.